Analysis of Communication Strategies of Hajj and Umrah Travel Agencies in Building Pilgrims' Trust Through Digital Media: A Case Study of PT. Assunniyah Al-Jauhari - Ahmadi, Eva Shinta Aisyah; Sudahri (Yayasan Ilomata, 2025)
Digital communication has become a fundamental element in the marketing and trust-building strategies of Hajj and Umrah travel agencies, shaping customer perceptions, engagement, and brand credibility. As prospective pilgrims increasingly rely on websites, social media, and digital platforms for information, agencies must adopt effective digital communication strategies to maintain transparency and build trust. This study investigates how digital communication strategies influence customer trust in Hajj and Umrah services. This study contributes to the literature by analyzing verbal and non-verbal digital communication strategies, two-way communication models, and trust-building mechanisms through the lens of the Elaboration Likelihood Model (ELM) and Two-Way Communication Theory. This study employs a qualitative case study approach, focusing on PT. Assunniyah Al-Jauhari Wisata, a Hajj and Umrah travel agency in Jember, East Java. Findings indicate that digital communication strategies are most effective when they incorporate transparency, customer engagement, and interactive dialogue. PT. Assunniyah successfully utilizes websites, social media, customer testimonials, and direct messaging platforms to establish credibility and maintain customer trust. The study highlights the importance of real-time customer interactions via WhatsApp, social media storytelling, and live consultation sessions in strengthening agency-pilgrim relationships. This study concludes that effective digital communication in the Hajj and Umrah industries must be interactive, transparent, and customer-centric to foster trust, loyalty, and positive customer perception. This study implies that Hajj and Umrah travel agencies need to optimize interactive and transparent digital communication. Using AI chatbots, real-time engagement, and social media analytics can strengthen trust and service credibility.